STUDENT`S UPBRINGING IN POLI-ETHNIC ORGANIZATIONS OF CHERNIVTSI UNIVERSITY (1875-1914) - Maryna Kozhokar (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
The author considers the main structural components of the students' upbringing in poly-ethnic associations of Chernivtsi University, namely, defines the purpose, tasks, means and features of educational activities in them. The researcher analyzes these system-forming factors in the context of bringing up a representative of the youth in the international conservative associations «Austria» and «the Academic Reading Room», which were operating at the most powerful Bukovynian educational institution during the Austro-Hungarian and Romanian periods. It has been acknowledged that from the first days of the university's activity there was a tendency of the emergence of academic associations. The representatives of the teaching staff actively participated in the organization and activities of these associations. In addition, the core task of the societies of such a format was the creation of an «Austrian student» - a devoted to the crown, educated and disciplined, elite young representative of the nation. Moreover, such representatives embodied the entire population of the Austro-Hungarian Empire, such a nationally impoverished nation, without its own customs and traditions of. The study emphasized that, despite the absence of officially established areas of «Austria's» activity, the analysis of the content of educational work allowed the author to distinguish their leading course that is cultural and educational orientation. Accordingly, education was carried out through general lectures and conversations with mandatory discussion of the report topic, the joint celebration of state and religious holidays with the official and entertaining part. The author concludes that associations mostly played the role of educational and entertainment clubs with a modern library and a certain general purpose - communication with interesting personalities and discussion of events in a cozy atmosphere. However, the author stresses the impossibility of leveling out the role of the first poly-ethnic societies of students of Chernivtsi University in the direction of bringing up an educated, able to rally for the sake of the great goal, advanced young people of the region.